The value of bile acid spectrum in the evaluation of hepatic injury in children with infectious mononucleosis caused by Epstein Barr virus infection - Shen, Ren; Zhou, Yan; Zhang, Lintao; Yang, Shanpu (Frontiers in Pediatrics, 2023)
Background Infectious mononucleosis (IM) is an acute infectious disease, caused by Epstein-Barr virus (EBV) infection, which can invade various systemic systems, among which hepatic injury is the most common. In this study, ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to detect serum bile acid spectrum in IM children quantitatively, and to investigate its role in the early assessment of hepatic injury. Methods This case-control study was conducted at Yuhuan People's Hospital. A total of 60 IM children and 30 healthy children were included in the study. Among 60 children with IM, 30 had hepatic injury, and 30 without hepatic injury. The clinical and laboratory data were analyzed, and the serum bile acid spectrum and lymphocyte subsets were evaluated in the three groups. Results There were statistically significant differences in cholic acid (CA), chenodeoxycholic acid (CDCA), deoxycholic acid (DCA), lithocholic acid (LCA), glycochenodeoxycholic acid (GCDCA), glycodeoxycholic acid(GDCA), glycolithocholic acid (GLCA), taurocholic acid (TCA), taurochenodeoxycholic acid (TCDCA), taurodeoxycholic acid (TDCA), ursodeoxycholic acid (UDCA), glycoursodeoxycholic acid (GUDCA), tauroursodeoxycholic acid(TUDCA), percentage of NK cells, CD4+ and CD8+ in IM hepatic injury group, without hepatic injury group, and the healthy control group (P < 0.05). The percentage of NK cells was positively correlated with TCA (P < 0.05); it was negatively correlated with CDCA, DCA, LCA, GCDCA, GDCA, GLCA, TDCA, UDCA, GUDCA, TUDCA (P < 0.05). CD4+ was positively correlated with CA, TCA and TCDCA (P < 0.05); it was negatively correlated with CDCA, DCA, LCA, GCDCA, GDCA, GLCA, TDCA, UDCA, GUDCA and TUDCA (P < 0.05). CD8+ was positively correlated with CDCA, DCA, LCA, GCDCA, GDCA, GLCA, TDCA, UDCA, GUDCA and TUDCA (P < 0.05); it was negatively correlated with CA, TCA and TCDCA (P < 0.05). ROC curve analysis showed that CD8+, GDCA and GLCA had high predictive value for hepatic injury in IM patients. Conclusions UPLC-MS/MS method can sensitively detect the changes in serum bile acid spectrum before hepatic injury in children with IM, which is helpful for early assessment of hepatic injury in children with IM. The changes in lymphocyte subsets in IM children are related to some bile acid subfractions, which may be related to IM hepatic injury.